Choreographing Compassion: A Clinical Adventure of Rhythms - Yopst, Charles George (Journal of pastoral care & counseling, 2015)
Compassion is a primary catalyst motivating positive human relationships, especially of those less fortunate. Our rhythms Expand-Contract of our own non-verbal body joints movements and of the law of counter-balance, enable us to identify which of nine innate affects-emotions is directing the body's movements. With this reading, a trained person can synchronize choreography of these into fully authentic compassion between two or more persons. Primary references for this are the late Silvan S. Tomkins's four volumes “Affect Imagery Consciousness,” and choreographers the late Rudolf Laban, Warren Lamb, Irmgard Bartenieff, and Marian Chace. Professionals, clinicians, and laity counselors can all use these.